Moderate, extreme, or both? How voters respond to ideologically unpredictable candidates. (February 2018) - Rogowski, Jon C.; Tucker, Patrick D.
Abstract: Candidates and parties often face a choice between endorsing policies that appeal to their core constituencies or generate support from more diverse groups of voters. While the latter strategy may make overtures to a wider set of citizens, existing literature says little about how the overall mix of issue positions affects electoral support. We argue that candidates who endorse diverse sets of policy positions appear unpredictable to voters and incur subsequent electoral penalties. Using data from the 2006 congressional elections, we find that ideological predictability substantially increases electoral support at both the individual and aggregate levels and that voters perceive greater ideological congruence from more predictable candidates. Our results have important implications for candidate and party strategies and suggest that voters are responsive to the mean and the variance of candidates' policy stances.